CASE STUDY IN SOCIAL RESEARCH : history, methods and applications. - Sena, Barbara ([S.l.] : ROUTLEDGE, 2023)
The Case Study in Social Research proposes and develops an innovative, rigorous, and up to date methodological clarification of the case study approach in the social sciences to consistently and consciously apply it to different fields of social research. It aspires to provide the reader not with a set of prescriptive rules, but rather with a methodological awareness' of the complexity and peculiarity of applying a case study, so that they may carefully evaluate the limits and potential of conducting this type of investigation. What is case study research in the sociological field really? How do we carry out a social inquiry of this type? How does it differ from other social research approaches? In answering these questions, this book leads the reader on a historical, epistemological, technical, and applicative path in the methodology of social research, by examining all aspects of the case study approach. The aim is to respond to as-yet still equivocal and misunderstood methodological issues, and provide a systematic illustration and exemplification of the case study approach, beginning from its sociological and methodological roots, its research design, and on through to its preparation and administration. Space is also dedicated to specifically and practically understanding the differences between the case study and the other social research approaches, with which it is often confused in literature, such as ethnographic research, grounded theory, or qualitative research. This book is suitable for upper level undergraduate and postgraduate students in the social sciences, and as a supplementary textbook to primary methods texts, as well as for social researchers, and other practitioners and academics with a firm grounding in social research methodologies.
Content provider: Taylor & Francis.
Vendor-supplied catalog record.
Keywords: Social sciences -- Research; Print books